PESANTREN SEBAGAI BASIS PENDIDIKAN SPRITUAL DALAM PEMBENTUKAN KARAKTER JATI DIRI MANUSIA - Moh Sakir (IAIN Ponorogo, 2015)
Abstract: In Islamic boarding schools, teachers do not only transfer religious sciences to the students, but also transform the importance of spiritual education as the first step in building human identity. Human beings have been already giveninnate essential elements by Allah as perfect complementsto be his vicegerent or khalifafilardli. To carry out this task, they must know in advance the principal elements or components that affect human spiritual characters. These componentsare the heart, intellectual and passion. These three components can be developed or trainedin sequence process of learning so that they know how to educate their heart, intellectual and passion, and eventually these lead their awareness as human beings who havepersonal identity as spiritual in nature. وأ خيشلا هب ماق ،بسحف بلاطلا ناهذأ لىإ ةينيدلا تامولعلما لقنت لا “ نيترنسب “ ةيوبترلا ةسسؤلما تناك سفن في تناك .ناسنلإا ةيصخش نيوكت في لىوأ ةوطخك ةيحورلا ةيبترلا ةيمهأ كلذك سردت اهنكل ،يهايك هذه ءادأ فيو .هضرأ في للها ةفيلخ هنوك في ةلمكم رصانعك للها اهقلخ تيلا ةيقيقح رصانع وأ عضوم ناسنلإا يه رصانعلا هذه .هيدل ةيحور ةعيبط في رثؤت ىتلا ةيساسلأا رصانعلا لاوأ فرعي نأ ناسنلإا ىلع ةفيظولا ناسنلإا ملعي تيح اهيف ةيبترلا ةيلمع قيبطت وأ اهتيمنت نكيم ةثلاثلا رصانعلا هذه .سفنلاو لقعلاو بلقلا .ةيحور ةرطف هل ناسنإك هسفن ةقيقح ناسنلإا ملعي يرخلأا فيو ،هسفنو هلقعو هبلق ةيبرت ةيفيك